2000
DOI: 10.1126/science.288.5470.1439
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of B Lymphocyte and Macrophage Development by Graded Expression of PU.1

Abstract: The ets family transcription factor PU.1 is required for the development of multiple lineages of the immune system. Using retroviral transduction of PU.1 complementary DNA into mutant hematopoietic progenitors, we demonstrate that differing concentrations of the protein regulate the development of B lymphocytes as compared with macrophages. A low concentration of PU. 1 protein induces the B cell fate, whereas a high concentration promotes macrophage differentiation and blocks B cell development. Conversely, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
475
4
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 650 publications
(511 citation statements)
references
References 25 publications
27
475
4
3
Order By: Relevance
“…We show in this study that TNF induced increased expression of the myeloid and lymphoid transcription factor, PU.1 [58,59]. The analysis of GATA-1/PU.1 interaction by immunoprecipitation showed that the TNF-mediated increase in PU.1 expression was associated with the formation of the GATA-1/PU.1 complex in the nuclear extracts from EPO-induced HSPCs.…”
Section: Discussionmentioning
confidence: 51%
“…We show in this study that TNF induced increased expression of the myeloid and lymphoid transcription factor, PU.1 [58,59]. The analysis of GATA-1/PU.1 interaction by immunoprecipitation showed that the TNF-mediated increase in PU.1 expression was associated with the formation of the GATA-1/PU.1 complex in the nuclear extracts from EPO-induced HSPCs.…”
Section: Discussionmentioning
confidence: 51%
“…In Table 2 the expression of investigated B-cell transcription factors in normal B-cell development is displayed. [12][13][14][15][16][17][18][19][20][21][22][23] Early B-Cell Transcription Factors: Pax-5 and PU.1 Expression…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with data from literature, PU.1 expression was observed in admixed histiocytes. 16 Mature B-Cell Transcription Factors: Oct2, BOB.1 and Bcl-6 Expression BOB.1 and Oct2 were detectable in all B-cell populations present in pseudo B-cell lymphomas and tonsils including mantle B-cells, germinal center B-cells and plasma cells. Expression of both Oct2 and BOB.1 was observed in 90% or more of the tumor cells in all 11 cases of primary cutaneous large B-cell lymphoma, leg type.…”
Section: Transcription Factors In Cutaneous B-cell Lymphoma Jj Hoefnamentioning
confidence: 99%
“…These developmental steps are controlled by diverse cytokines and transcription factors cooperating to achieve efficient generation of mature lymphocytes 154 . In early stages, both PU.1 and Ikaros control the balance between myeloid or lymphoid commitment of MMPs through regulation of different signaling receptors (FLT3, c-KIT and IL-7R) [157][158][159] . More committed, earliest B cell progenitor transition to pro-B cell depends on addi-tional transcription factors (E2A, EBF, PAX5 and BCL11A), which coordinately activate appropriate Bcell expression programs and immunoglobulin heavychain gene rearrangements [160][161][162][163][164][165] .…”
Section: Do Lymphoid Malignancies Arise From Mutations That Deregulatmentioning
confidence: 99%